A marriage of convenience; a simple food chain comprised of Lemna minor (L.) and Gammarus pulex (L.) to study the dietary transfer of zinc. (14th April 2014) - Lahive, E.; O'Halloran, J.; Jansen, M. A. K.
Abstract: Macrophytes contribute significantly to the cycling of metals in aquatic systems, through accumulation during growth and release during herbivory or decomposition. Accumulation of high levels of metals has been extensively documented in Lemnaceae (duckweeds). However, the degree of trophic transfer of metals from Lemnaceae to secondary consumers remains poorly understood. This study demonstrates that zinc accumulated in Lemna minor is bioavailable to the herbivore consumer Gammarus pulex . Overall, the higher the zinc content of L. minor, the more zinc accumulated in G. pulex . Accumulation in G. pulex was such that mortality occurred when they were fed high zinc‐containing L. minor . Yet, the percentage of consumed zinc retained by G. pulex actually decreased with higher zinc concentrations in L. minor . We hypothesise that this decrease reflects internal zinc metabolism, including a shift from soluble to covalently bound zinc in high zinc‐containing L. minor . Consistently, relatively more zinc is lost through depuration when G. pulex is fed L. minor with high zinc content. The developed Lemna–Gammarus system is simple, easily manipulated, and sensitive enough for changes in plant zinc metabolism to be reflected in metal accumulation by the herbivore, and therefore suitable to study ecologically relevant metal cycling in aquatic ecosystems.